The Effect of Flow on Lysis of Plasma Clots in a Plasma Environment - Sakharov, Dmitry V.; Rijken, Dingeman C. (Thrombosis and Haemostasis, 2000)
Fibrinolysis initially generates channels in an occluding thombus which results in blood flow through the thrombus. Since the impact of flow along the surface of a thrombus on thrombolysis has not been investigated in detail, we studied in vitro how such a flow affects lysis. Compacted and noncompacted plasma clots were used as model thrombi. With compacted clots, fibrin-specific lysis induced by alteplase in the outer plasma was accelerated about 2-fold by strong flow (arterial shear rate). Non-fibrin-specific lysis induced either by a high concentration of alteplase or by streptokinase was slow, was accompanied by rapid depletion of plasminogen in the outer plasma, and was only slightly accelerated by flow. With noncompacted clots, similar acceleration factors were documented, when mild flow (venous shear rate) was applied. Strong flow further accelerated fibrin-specific lysis, up to 10-fold as compared to lysis without flow, but paradoxically retarded non-fibrin-specific lysis. The data suggest that flow accelerates lysis by enhancing transport of plasminogen from the outer plasma to the surface of the clot. Both opposite effects of the strong flow were mediated by forceful intrusion of the outer plasma into the noncompacted clot due to flow irregularities. In the case of non-fibrin-specific lysis this resulted in the replacement of the plasminogen-containing milieu by plasminogen-depleted outer plasma in certain areas of the clot turning them into virtually unlysable fragments. This flow-enforced “plasminogen steal” may contribute to the relatively high percentage of incomplete thrombolysis (TIMI-2 grade flow) documented in a number of trials for non-fibrin-specific thrombolytic agents. In the case of fibrin-specific lysis, the effect of flow on the speed of fibrinolysis is always beneficial.
Keywords: Fibrinolysis; thrombolysis; plasminogen; flow; fibrin-specificity